Type 1 diabetes care delivery in Yaoundé, Cameroon: Social and political representations - Hervé B. Djiofack Kentsop; Christina Zarowsky; Julia E. von Oettingen (AOSIS, 2024)
Background: Increasing chronic diseases challenges the health systems of low- and middle-income countries, including Cameroon. Type 1 diabetes (T1D), among the most common chronic diseases in children, poses particular care delivery challenges. Aim: We examined social representations of patients' roles and implementation of T1D care among political decision-makers, healthcare providers and patients within families. Setting: The study was conducted in Yaoundé, Cameroon. Methods: Eighty-two individuals were included in the study. The authors conducted semi-structured interviews with policy makers (n = 5), healthcare professionals (n = 7) and patients 'parents (n = 20). Questionnaires were administered to paediatric patients with T1D (n = 50). The authors also observed care delivery at a referral hospital and at a T1D-focused non-governmental organisation over 15 days. Data were analysed using thematic content analysis and descriptive statistics. Results: Cameroonian health policy portrays patients with T1D as passive recipients of care. While many practitioners recognised the complex social and economic determinants of adherence to T1D care, in practice interactions focused on specific biomedical issues and offered brief guidance. Cultural barriers and policy implementation challenges prevent patients and their families from being fully active participants in care. Parents and children prefer an ongoing relationship with a single clinician and interactions with other patients and families. Conclusion: Patients and families mobilise experience and lay knowledge to complement biomedical knowledge, but top-down policy and clinical practice limit their active engagement in T1D care. Contribution: Children with T1D and their families, policy makers, healthcare professionals, and civil society have new opportunities to contribute to person-centred care, as advocated by the Sustainable Development Goals.